Effects of carbohydrate supplementation on aerobic exercise performance during acute high altitude exposure and after 22 days of acclimatization and energy deficit. Issue 1 (9th January 2020) - Bradbury, Karleigh E.; Berryman, Claire E.; Wilson, Marques A.; Luippold, Adam J.; Kenefick, Robert W.; Young, Andrew J.; Pasiakos, Stefan M.
Abstract: Background: The ergogenic effects of supplemental carbohydrate on aerobic exercise performance at high altitude (HA) may be modulated by acclimatization status. Longitudinal evaluation of potential performance benefits of carbohydrate supplementation in the same volunteers before and after acclimatization to HA have not been reported. Purpose: This study examined how consuming carbohydrate affected 2-mile time trial performance in lowlanders at HA (4300 m) before and after acclimatization. Methods: Fourteen unacclimatized men performed 80 min of metabolically-matched (~ 1.7 L/min) treadmill walking at sea level (SL), after ~ 5 h of acute HA exposure, and after 22 days of HA acclimatization and concomitant 40% energy deficit (chronic HA). Before, and every 20 min during walking, participants consumed either carbohydrate (CHO, n  = 8; 65.25 g fructose + 79.75 g glucose, 1.8 g carbohydrate/min) or flavor-matched placebo (PLA, n  = 6) beverages. A self-paced 2-mile treadmill time trial was performed immediately after completing the 80-min walk. Results: There were no differences ( P  > 0.05) in time trial duration between CHO and PLA at SL, acute HA, or chronic HA. Time trial duration was longer ( P  < 0.05) at acute HA (mean ± SD; 27.3 ± 6.3 min) compared to chronic HA (23.6 ± 4.5 min) and SL (17.6 ± 3.6 min); however, time trial duration at chronic HA was still longer than SL ( P  < 0.05). Conclusion: These data suggest that carbohydrate supplementation does not enhance aerobic exercise performance in lowlanders acutely exposed or acclimatized to HA. Trial registration: NCT, NCT02731066, Registered March 292, 016